RANCANG BANGUN SISTEM PERINGATAN KANTUK PADA PENGENDARA SEPEDA MOTOR BERBASIS FUZZY LOGIC - Daniel Moses Samosir; Aditya Bayu Setyaji; Ramdhani Ramdhani; Yusep Sukrawan (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Motorcycle riders are basically required to drive with awareness of orderly behavior on the road. However, the fact is that many motorbike accidents are still caused by negligence, one of which is drowsiness while driving. This research aims to develop a fuzzy logic-based drowsiness prevention tool for motorcyclists. This tool goes through 4 stages of testing, namely power supply, sensor, microcontroller and actuator. The results of testing are that the power supply on this tool functions well, the tools on the motorbike and helmet function well according to the program designed on the microcontroller, the pulse sensor designed for motorbikes does not function as it should, so for temporary research the Max sensor is used 30100 as a pulse reader, buzzer, vibrator and relay in this tool functions well and is more accurate compared to previous research according to the fuzzy rules that have been programmed. The use of sensors on the wrist has proven to be effective in detecting pulse, so that the accuracy of sleepiness readings is in line with pulse readings, namely 100%, which is a follow-up to previous research. Fuzzy logic on the device influences the microcontroller to work accurately according to what has been programmed.